Strengthening Students’ Character of Discipline and Responsibility Through the KKN Program at SDN 10 Kamang Baru - Amin, Muhammad; Suryati , Peni; Renza , Dika Rama; Arsi, Syofna; Falin, Wenny Septiana; Sari, Linda (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Character development in students has become a key focus in primary education, particularly in strengthening the values of discipline and responsibility. This research was motIated by the observation that students at SDN 10 Kamang Baru still show low levels of these character traits. To address this issue, the Community SerIIIce Program (KKN) was implemented as a strategy to instill and reinforce these values through educational actIities and exemplary behaIIIor by unIersity students. The objectIe of this study is to describe the impact of the KKN program on strengthening students’ character, specifically in terms of discipline and responsibility. This study employed a qualitatIe descriptIe approach, involIIIng 30 students from grades I to III, 3 classroom teachers, and 1 school principal as participants. Data collection techniques included observation, interIIIews, and documentation. The data were analyzed through data reduction, data display, and drawing conclusions. The results revealed a significant improvement in students’ discipline and responsibility after the implementation of the KKN program. Approximately 83% of students showed improved discipline, such as punctuality and adherence to school rules, while 76% of students demonstrated increased responsibility, such as completing assignments on time and maintaining classroom cleanliness. Teachers and the principal confirmed that the KKN program had a positIe impact on students’ attitudes and behaIIIor, particularly through habitual practices, value reinforcement, and direct modeling by KKN participants. Conclusion: The KKN program effectIely strengthens the character of discipline and responsibility among elementary school students. This program can serve as a model for collaboration between higher education institutions and schools in developing the character of future generations with integrity.